Modi' a textbook of medical jurisprudence and toxicology - Modi, Jaising P. (LexisNexis Butterworths Wadhwa, 2012)
This book has been the reference tool for medical and legal professionals and just as well has helped the investigating agency to stay focused on what are essential and to know what data is important to be collected from the scence of crime. This monumental work has two parts which are revised by specialist contributors from diverse fields. This edition has been revised keeping in view the needs of the new forensic medicine syllabus, judicial observations and the concerns of the senior forensic medicine experts and the readers will find our present edition helpful both for learning and applying the nuances of the subject in practice.